Analisis Peran Pelatih dalam Pengembangan Mental Juara - Haq, Amalia Dhiaul; Priambodo, Anung; Mulyono; Darisman, Eka Kurnia (MAN Insan Cendekia Jambi, 2025)
This study analyzes the role of coaches in developing athletes’ champion mentality, emphasizing that sports achievements are not solely determined by physical and technical abilities but are also strongly influenced by mental toughness, motivation, and self-confidence. The research employs a descriptive qualitative approach with data collection techniques including questionnaires, observations, and interviews. The focus of the study covers the role of coaches as psychological mentors, motivators in building self-confidence, as well as enforcers of discipline and mental resilience. The findings indicate that coaches play a crucial role in shaping athletes’ champion mentality, not only by providing technical guidance but also by serving as psychological mentors, motivators, and trainers of discipline and mental toughness. These results are expected to provide a more comprehensive understanding of the psychological dimensions of coaching while identifying best practices to cultivate athletes who excel physically and possess a strong champion mentality.